Pengaruh Pesan Keagamaan Dalam Nadham Maulid Al-Dhiyâ’ Al-Lâmi’ Terhadap Jamaah Majelis Taklim Al-Hidayat Gampong Peulanggahan Banda Aceh; Kajian Ritual Effect - Syarifuddin; Cut Masthura Rahmatillah; Abd Razak; Rahma Salbiah (An-Nahdah Al-'Arabiyah)
This study focuses on analyzing the religious messages in the ritual recitation of Nadham Maulid Al-Dhiyâ’ Al-Lâmi’, its impact on the congregation of Al-Hidayat Majelis Taklim and the community, as well as the motives and strategies for its preservation using the ritual effect approach. This research employs a qualitative method with a public opinion survey approach, gathering data through observation, interviews, and documentation studies. Data analysis is conducted through data reduction, presentation, and conclusion drawing, while data validity is ensured through continuous observation, increased rigor, and triangulation. The findings are as follows: First, the content includes messages of monotheism, praise for the Prophet, nobility, lineage, praises for the birth, and prophetic history; second, the religious impact on the lives of the congregation and the Acehnese community includes increased faith, love for the Prophet, adherence to Allah’s Sharia and the Prophet’s Sunnah, blessed life, improved morals, psychological therapy, and strengthened social relationships; third, the ritual art of reciting Nadham Maulid Al-Dhiyâ’ Al-Lâmi’ can be preserved due to the attraction to the familial network of the Prophet known as Ahlul Bait, as well as the traditional Hadrah music